Paul's language of Zēlos : monosemy and the rhetoric of identity and practice - Lappenga, Benjamin J. (Biblical Interpretation Series, 2016)
In Paul's Language of Ζῆλος , Benjamin Lappenga harnesses linguistic insights recently formulated within the framework of relevance theory to argue that within the letters of Paul (specifically Galatians, 1-2 Corinthians, and Romans), the ζῆλος word group is monosemic . Linking the responsible treatment of lexemes in the interpretive process with new insight into Paul's rhetorical and theological task, Lappenga demonstrates that the mental encyclopedia activated by the term ζῆλος is 'shaped' within Paul's discourse and thus transforms the meaning of ζῆλος for attentive ('model') readers. Such identity-forming strategies promote a series of practices that may be grouped under the rubric of 'rightly-directed ζῆλος'; specifically, emulation of 'weak' people and things, eager pursuit of community-building gifts, and the avoidance of jealous rivalry.